If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x + -10 + x + -5x + 1 = 14 + 3x + -8 + -1 Reorder the terms: -10 + 1 + 1x + x + -5x = 14 + 3x + -8 + -1 Combine like terms: -10 + 1 = -9 -9 + 1x + x + -5x = 14 + 3x + -8 + -1 Combine like terms: 1x + x = 2x -9 + 2x + -5x = 14 + 3x + -8 + -1 Combine like terms: 2x + -5x = -3x -9 + -3x = 14 + 3x + -8 + -1 Reorder the terms: -9 + -3x = 14 + -8 + -1 + 3x Combine like terms: 14 + -8 = 6 -9 + -3x = 6 + -1 + 3x Combine like terms: 6 + -1 = 5 -9 + -3x = 5 + 3x Solving -9 + -3x = 5 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -9 + -3x + -3x = 5 + 3x + -3x Combine like terms: -3x + -3x = -6x -9 + -6x = 5 + 3x + -3x Combine like terms: 3x + -3x = 0 -9 + -6x = 5 + 0 -9 + -6x = 5 Add '9' to each side of the equation. -9 + 9 + -6x = 5 + 9 Combine like terms: -9 + 9 = 0 0 + -6x = 5 + 9 -6x = 5 + 9 Combine like terms: 5 + 9 = 14 -6x = 14 Divide each side by '-6'. x = -2.333333333 Simplifying x = -2.333333333
| 4xy-5y+2=0 | | -2x=3(x-5)+6 | | 3x-10=-4x+22 | | 3p(p-1)=18 | | 7x=50-1 | | 3(-8)+[6(-2)]= | | 3n^3-4n^2+n=0 | | 3(-8)+[16(-2)]= | | -5(4x+5)=4+2(4x-8) | | n^2+2n+24=0 | | 3(2z+7)+4=5(z-3) | | 1=3x-21 | | (y^2+2y)+(3y^2+4y+2)=0 | | 7(x+1)=6-2(7x+7) | | x^2=6x+10 | | 3X+3=2X+2 | | 9+6x+4-x=16+7-5 | | k=LMN | | 50x+20(x+6)+10(x+6)+5*2*(x+6)=1140 | | 13-4=-6x+17 | | 4x^3+x^2-36x-9=0 | | 6(-3x+1)=-10(x+1)+16-8x | | 2x^2+4x+20=0 | | 9x+8-10x+2=8x-9x-3 | | 5x+1=1+5x | | (n-2)+(n-1)+5n=47 | | 3x+10=3x+8 | | 7x=8x^2 | | 15(c+3)+6=61 | | x^4-2x^3+x^2-8x-12=0 | | 7(3x-5)+3(16-4x)=4(2x+5)-11 | | x^2+y^2+3x-2y-1=0 |